Aplikasi Markerless Augmented Reality Dewata Nawa Sanga Berbasis Android - I Wayan Andis Indrawan; I Putu Agung Bayupati; Desy Purnami Singgih Putri (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Udayana, 2017)
The culture of Hinduism in Bali is very preserved and maintained by the Hindus in Bali to remain dignified. Dewata Nawa Sanga is one of the Hindu Religion Concept embraced by the Hindus in Bali. Dewata Nawa Sanga means nine deities as a manifestation of God in charge of guarding and controlling the nine wind direction. The application of Augmented Reality Dewata Nawa Sanga developed to increase the knowledge of Hindus in Bali about the concept of Dewata Nawa Sanga, through a learning medium considering the importance of Dewata Nawa Sanga for Hindus in Bali. The application of Augmented Reality Dewata Nawa Sanga developed using the markerless method, so users simply rotate the Android devices to see the position of Deity in the nine wind directions and to know the information of each of the deities. Application of Augmented Reality Dewata Nawa Sanga provides education about detail elements about each Deity in nine wind direction through Information View feature in narrative form. The resulting application indirectly educates the user to know the direction of the controlled and guarded by nine Deity as a manifestation of the god through Augmented Reality display by using gyroscope sensors.